New Innovation in English Language Teaching: Revealing Concepts and Applications of ECO-ELT - Jepri Ali Saiful (Tell : Teaching of English Language and Literature Journal, 2020)
Nature is essential to our lives. Unfortunately, the widespread influence of modernism and industrial progress results to environmental pollution and destruction of the nature. Ecocriticism study is thereby projected to awaken self-awareness and sense of belonging to human beings towards the nature. This study is thus aimed to discuss and integrate the nature of Ecocriticism in English language teaching, particularly in the applications in lesson plans and teaching materials. The results show that Ecocriticism disseminates the issues of environmental crisis and the necessity of saving the nature and therefore taking the roles of literature to lead people virtue and right is necessary. English teachers is unequivocally became â€œgreenâ€ moral agents. They have new responsibilities to use literature to not only teach English skills and components, but also to embed and spread the virtues of loving the nature to the students. Thus, the concept of Eco-ELT derived from the terms of Ecociticism and English Language Teaching (ELT) was coined and introduced. Eco-ELT worked on a basis postulate that literary works could be an avenue to teach English and ecology at the same time. The selections and applications of the literary works therefore mattered. This study provided samples and principles of designing eco-lesson plan and selecting and designing eco-teaching materials. Importantly, this study expounded the areas of eco-English materials necessary for English teachers.